Neuroprotective Impact of Bioactive Flavonoids in Scopolamine Induced Behavioral and Biochemical Paradigms in Mice - Atul Deshmukh, Swapnil Goyal, Tanaji Nandgude (International Journal of Advanced Science and Technology, 2020)
Neurons are the fundamental building block of nervous system; their job is to transmit signals, which is why they are so significant. The progressive, selective loss of anatomically or physiologically linked neuronal structures is a hallmark of neurodegeneration, which leads in a wide spectrum of neurodegenerative illnesses.Two common instances are Alzheimer's disease (AD) and Parkinson's disease (PD). According to World Alzheimer Statistics, there were 47 million people worldwide with Alzheimer's disease in 2016, with that number anticipated to climb to more than 131 million by 2050.Despite the fact that it is India's main cause of disability, the growth and progress of neuroepidemiology has been documented throughout the last four decades, with historical milestones emphasized; yet, despite the fact that it is India's major cause of disability, there is no definitive solution.Because Alzheimer's is a complex condition. Natural bioactive compounds have a wide spectrum of therapeutic properties and can be utilized to treat chronic diseases like Parkinson's and Alzheimer's.In this propose investigation centralizing on two such most promising bioactive flavonoids like, Andrographolide (AG) and Hesperidin (HSD) and with the goal of identifying the potential synergistic impact at low dose adjacent to Scopolamine administration (1mg/kg, i.p.) for 7 days. The current study's findings suggest that intraperitoneal scopolamine administration causes neurobehavioral and biochemical changes in mice that are similar to those seen in Alzheimer's disease.Individual and combined treatment of mice with AG and HSD is anticipated to provide significant neuroprotection mediated by its antioxidant characteristics, and provides a compelling rationale for improved clinical control of Alzheimer's disease.